SOKA CRAB DISEASE DIAGNOSIS SYSTEM USING CERTAINTY FACTOR METHOD - Alfariza, Muhammad Arjuna; Sihombing, Marto; Prahmana, I Gusti (Journal of Mathematics and Technology (MATECH), 2024)
Soka crabs (soft cell crabs) are crabs in the molting phase or soft shell crabs. Crabs in this phase can be used as a whole so that this is an advantage of soka crabs (Sayuti, 2018). To get the maximum benefit, soka crab cultivation should not be done on the side or just a subsistence activity. Soka crabs can live in high stocking densities. Therefore, soka crab cultivation will provide more benefits if done intensively. But there are also problems that arise in soka crabs. The problem is the failure of this crab rearing activities. One of the causes of failure of this activity is due to disease factors. The emergence of disease disorders in crabs is a risk that must always be anticipated. Therefore, the authors will create an application system that can diagnose diseases that attack the soka crab. In the application, users only need to answer questions given by the application to be able to find out the disease that is attacking the soka crab. With the creation of this application people know about how to deal with the problem of disease in soka crabs, for that with this application the problem of lack of experts can be resolved. From the results of the analysis performed manually obtained the value of the certainty factor from the input of symptoms leading to Aeromonas spp is 73.1264%.